2018
DOI: 10.5194/angeo-2018-125
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quarterdiurnal signature in sporadic E occurrence rates and comparison with neutral wind shear

Abstract: Abstract. The GPS radio occultation (RO) technique is used to study sporadic E (ES) layer plasma irregularities of the Earth’s ionosphere on a global scale using GPS signal-to-noise ratio (SNR) profiles from the COSMIC/FORMOSAT-3 satellite. The maximum deviation from the mean SNR can be attributed to the height of the ES layer. ES are generally accepted to be produced by ion convergence due to vertical wind shear in the presence of a horizontal component of the Earth magnetic field, while the wind shear is pro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 53 publications
(84 reference statements)
2
3
0
Order By: Relevance
“…Besides, as the latitude changes from mid-latitude to low-latitude, the height of EsOR gradually decreases from above 100 km to below 100 km (Figure 3). This result supports the previous views of Jacobi et al (2019) and Qiu et al (2021) and can be attributed to the altitude-latitude distribution of wind shear (Figure S4) controlled by the atmospheric tides (Liu et al, 2019a;Qiu et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Besides, as the latitude changes from mid-latitude to low-latitude, the height of EsOR gradually decreases from above 100 km to below 100 km (Figure 3). This result supports the previous views of Jacobi et al (2019) and Qiu et al (2021) and can be attributed to the altitude-latitude distribution of wind shear (Figure S4) controlled by the atmospheric tides (Liu et al, 2019a;Qiu et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…This result supports the previous views of Jacobi et al. (2019) and Qiu et al. (2021) and can be attributed to the altitude‐latitude distribution of wind shear (Figure ) controlled by the atmospheric tides (Liu et al., 2019a; Qiu et al., 2021).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…found in the upper E region (above 110 km) in the low latitude region by using the Arecibo ISR observations (Morton et al, 1993;Tong et al, 1988). Recently, Jacobi et al (2019) also reported a 6-h periodicity, which shows good agreement between phases of the 6-h periodicity in sporadic E and the negative vertical shear of the zonal wind for all seasons except for summer in the mid-latitude region at Collm (51.3°N, 13.0°E). In recent years, observations obtained from radio occultation (RO) systems have been widely used in the detection and analysis of sporadic E layers.…”
Section: Plain Language Summarymentioning
confidence: 71%